Strangers at Home: Identity Negotiation Practices among Ethnic Chinese in Madura, Indonesia - Hidayat, Medhy Aginta; Farid, Mohtazul (The Journal of Society and Media, 2021)
This study examines the identity negotiation practices among ethnic Chinese in inter-ethnic relations in Madura, Indonesia. Even though ethnic Chinese have been living in Madura for quite a long time, they are still often considered as œstrangers by most of native Madurese. This study used qualitative data from literature review, field observations, and in-depth interviews with fifty informants of the ethnic Chinese who were born and lived in Madura. This study found that the practice of identity negotiation carried out by the ethnic Chinese in Madura includes several ways: using local language in daily conversation, changing their Chinese names into native Madurese names, practicing the Madurese indigenous cultural traditions in daily life, embracing Islam the majority religion of the native Madurese as their new religion, and marrying native Madurese men or women. The findings of this study corroborated prior studies that in unequal inter-ethnic relations, the ethnic minority often have to sacrifice themselves to be accepted by the ethnic majority. Moreover, ethnic minorities often have to negotiate identities, by hiding their master identity and highlighting other minor identities in order to be accepted and coexist with the ethnic majority.